1991
DOI: 10.1007/bf01344354
|View full text |Cite
|
Sign up to set email alerts
|

Temporal genetic variation in subpopulations of bicolor damselfish (Stegastes partitus) inhabiting coral reefs in the Florida Keys

Abstract: Abstract. In 1986 we observed significant genetic heterogeneity among samples of bicolor damselfish (Stegastes partitus) from geographically proximate coral reefs in the Florida Keys. This result was in contrast to results of virtually all previous studies of coral reef fishes. To assess temporal stability of localized genetic differentiation, we resampled reefs in 1989. Within approximately two generations, allele frequencies at the most differentiated locus, ACO-I*, had changed by as much as 0.65, resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 15 publications
0
31
0
1
Order By: Relevance
“…Lacson (1992) found no genetic structure across the entire Caribbean using allozyme markers and OspinaGuerrero et al (2008) found similar results using microsatellite markers in the Colombian-Caribbean. However, other studies found genetic heterogeneity among populations of S. partitus in the Florida Keys (Lacson et al 1989), but the differentiation was attributed to population bottlenecks (Lacson & Morizot 1991). Furthermore, recent microsatellite analyses showed weak population structuring within the Caribbean Antilles (Purcell et al 2009), the Bahamas (Christie et al 2010) and within the western Caribbean (Salas et al 2009).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Lacson (1992) found no genetic structure across the entire Caribbean using allozyme markers and OspinaGuerrero et al (2008) found similar results using microsatellite markers in the Colombian-Caribbean. However, other studies found genetic heterogeneity among populations of S. partitus in the Florida Keys (Lacson et al 1989), but the differentiation was attributed to population bottlenecks (Lacson & Morizot 1991). Furthermore, recent microsatellite analyses showed weak population structuring within the Caribbean Antilles (Purcell et al 2009), the Bahamas (Christie et al 2010) and within the western Caribbean (Salas et al 2009).…”
Section: Discussionmentioning
confidence: 96%
“…However, Hedgecock (1994) compiled evidence across a variety of taxa that supports the sweepstakes hypothesis. Finally, pre-settlement variation in recruit composition driven by the mixing of sub-populations in the plankton (evidence for the variable source hypothesis) was suggested to explain temporal patchiness in haddock (Purcell et al 1996), as well as to explain small-scale variation in Stegastes partitus populations using allozyme and microsatellite markers (Lacson & Morizot 1991, Roberts 1997, Hepburn et al 2009). …”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
See 2 more Smart Citations
“…This is suggested by the lack of significant differences observed in development rates of induced tumors in fish from low compared to high tumor prevalence reefs. Furthermore, studies of population genetics of bicolor damselfish in Florida as well as this and other manne fish species in the Southeast Atlantic region have shown a complete lack of any detectable population substructure throughout the entire Caribbean basin, Florida and the Bahamas (Lacson & Morizot 1991). Thus, there is no evidence to support the involvement of any genetic factors (heritable mechanisms) in DNF.…”
Section: Viral Carcinogenesis Has Been Documented In Fishesmentioning
confidence: 91%